Love my rifle more than you young and female in the U.S. Army - Williams, Kayla 1976- (Norton, 2005)
An account of the experiences of women soldiers relates the author's decision to enlist, her relationship with a Palestinian boyfriend, her witness to the events of September 11 as portrayed on Arabic television, and her deployment to Iraq.